ASSESSMENT ON EFFECTS OF DIESEL OIL ON TWO ALGAL SPECIES CHAETOCEROS MUELLERI AND SKELETONEMA COSTA TUM - Du, Hoang Trung (Vietnam Journal of Marine Science and Technology, 2009)
The effects of diesel oil on the algal species are carried on C. muelleri and S. costatum by using toxicology test. The results showed the different effects of diesel concentrations on parameters (such as: density cells, chlorophyll a and primary productivity) of two algal specie S which are domillallt in coastal areas. Using th e indices of toxicity testi11g to assess the toxic of diesel oil on two algal species which can be tolerated "tress" differellt levels of oil col/tamillatioll. The toxicity indices which is poiso11ed 011 inliibitio11 of algal growth rates when were exposed with oil pollution such as: IC 25 is 2 24.8J.igWSFIL:t42.4 for C. muelleri species a11d 454 JtWSFIL:tl 8 for S. cos tatum species, respectivel y. Me a l/whil e, the effects of toxicity diesel oil on 50% i11hibition of algal growth r a t es (IC 50) obtained higher than 500J.igWSF/Lfor both algal species. Affects of diesel oil were also showed through some parameters such as chlorophyll a and primary productivity concent r ations which were rapidly reduced while oil contaminatioll is increased, respectively. The 50% reduced rates of parameters occurred at conce11trations > 125 μWSF/L for C. muelleri and > 250μWSF/L for S. costatum algal species that it’s was compared with controlled experiments. At the same time, based on the advantage of chlorophyll a parameter, it was examined to use in toxicity test for chemical poisons on algal testing and we recognized that it can be applied for assessing the waters with sign of oil pollutant . Moreover, it’s very usefitl in early warning ecological risk in the coastal waters where frequently occur oil pollution